(untitled) (South East Asia Journal of Public Health, 2017)
Nowadays, Social Network (SN) is one of the essential tools of people especially young and adolescents. In consequence, there are so many controversial things on advantages and disadvantages of SN. In Myanmar, the rate of mobile phone users and internet users is on the increase today. This is a cross-sectional study conducted to the university students at Kyaukse University from June to November, 2015. In total 400 students who are aged between 16-23 years were randomly selected and interviewed with pretested structured questionnaires. The aim of this study is to determine the prevalence of Social Network Addiction (SNA) and the prevalence of anxiety. Furthermore, this study also found out SNA related to anxiety among students. Among the students, 110 students (27.5%) addicted to SN and 146 students (36.5%) suffered from anxiety. There is significant association between SNA and anxiety. Among the social network addicted users, 59.1% suffer from anxiety (χ²=33.408, p<0.001). Most of the students who used SN addicted to SN. The students addicted to SN, duration of SN more than 3 years, SN using hours more than 4 hours per day, using Facebook and Google suffer from anxiety. According to the findings in this study, there is a positive association between SNA and anxiety. So parents, teachers and other authorities should be aware and involved in checking and controlling the internet use of the students. In addition, the similar researches should be encouraged in different population and different age groups to explore other side effects of SNA. South East Asia Journal of Public Health Vol.7(1) 2017: 23-28